HFE gene mutation (C282Y) and phenotypic expression among a hospitalised population in a high prevalence area of haemochromatosis. (1st October 2000) - Distante, S; Berg, J P; Lande, K; Haug, E; Bell, H
Abstract : BACKGROUND: Previous studies have shown that up to 0.5% of the Caucasian population is homozygous for the HFE gene C282Y mutation. High prevalence values have been reported in Northern Europe. To what extent the presence of this mutation is associated with overt clinical haemochromatosis is unclear. AIM: To determine the prevalence of the C282Y allele in a hospitalised population of an acute medical department, and study the phenotypic expression in the homozygotes. METHODS: Blood samples were obtained from 2027 hospitalised patients; 1900 Caucasians and 127 non-Caucasians. Serum iron, transferrin, and ferritin were measured at admission. The presence of the HFE gene mutation was determined by polymerase chain reaction based analysis. Follow up fasting blood samples were obtained from patients homozygous for the mutation. RESULTS: Fourteen of the 1900 Caucasian subjects (0.74%) were homozygous and 224 (11.8%) were heterozygous for the C282Y mutation, including 32 subjects (1.7%) who were compound heterozygous for the C282Y and H63D mutations. Ten of 14 (71%) homozygous patients displayed mild to moderate biochemical expression of haemochromatosis with a serum ferritin level <550 μg/l, two (14%) patients were "non expressing", and two of five in whom liver biopsies were carried out had cirrhosis, including one with advanced hepatocellular carcinoma. CONCLUSIONS: The prevalence of C282Y homozygosity in a hospitalised population was 0.74%. However, the majority of homozygous patients displayed mild to moderate biochemical expression. C282Y mutation screening may detect individuals that do not develop haemochromatosis. Transferrin saturation and ferritin, which are used as first line screening in haemochromatosis, may be highly unreliable in the presence of an inflammatory process.